Projectivity on y-closed Submodules - Al-Bahrani, B. (Iraqi Journal of Science, 2024)
In this notion we consider a generalization of the notion of a projective modules , defined using y-closed submodules . We show that for a module M = M1M2 . If M2 is M1 – y-closed projective , then for every y-closed submodule N of M with M = M1 + N , there exists a submodule M`of N such that M = M1M`.